An Investigation on the Performance of Random PWM Controlled Converters - Jadeja, R.; Ved, A.; Chauhan, S. (Engineering, Technology & Applied Science Research, 2015)
This paper provides an insight on various random pulse width modulation techniques and their effect on spreading the harmonic spectrum for various applications like drives, hybrid electric vehicles and renewable energy sources, for two level as well as three level inverter. Acoustic noise reduction, electromagnetic interference conducted and torque ripple are obvious advantages of random pulse width modulation (PWM). PWM converters with multilevel topology can meet with global quality standards for power supplies. The random PWM technique provides additional advantages. Among others, it may be implemented to achieve switching loss equalization in power switches for cascaded H-Bridge multilevel inverters. This paper provides in depth understanding for different random PWM techniques and their applications.